Denormalization of the Global Order during the Covid 19 Pandemic and Its Impact on the Industrial Era 4.0 - Dwi Ardiyanti; Fitriana Harahap (Resolusi: Jurnal Sosial Politik, 2021)
This paper is a response from the shift of the global order that had focused on the mandate of international organizations to become more and more parties who played an important role in handling the Covid-19 pandemic, even at the level of the grassroots movement. This research focuses on increasing the use of digital access during the pandemic. The authors try to convey his analysis of the shift in the global order and its impact in the industrial era 4.0. The authors also analyze the challenges faced in using digital post Covid-19. This paper departs from the existence of a new phenomenon that emerged during the Covid 19 pandemic around the world, namely the learning from home, work from home, as well as everything new in the digitization system which then becomes a new normal behavior globally. The purpose of this paper is to analyze and explain the impact of the Covid 19 pandemic in the era of industry 4.0, both in the challenges to the potential for digitalization.